The Diversity of Plants for Berangas Materials - Dias Pratami Putri; Ervizal A. M. Zuhud; Rachmad Hermawan; Rusmin Tumanggor (Media Konservasi)
Betangas as a culture of the Sintang Malay community is a steam bath that has been done for generations. However, the current knowledge about betangas has not been well documented. This study aimed to determine the utilization of plants as a traditional medicine through betangas by the people of Sintang City. This research used structured interview method with respondent determination by snowball sampling. The results of the study identified 10 species used in betangas. Where 4 out of 10 species have been cultivated by the community to support the sustainability of the betangas plant.   Keywords: betangas, plant medicine, traditional spa